TECHNOLOGY FOR OBTAINING NEW STRUCTURES OF TWO-LAYER KNITTED TEXTURES (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Joint ventures specializing in the production of knitwear in our country use synthetic threads for the production of knitwear to the required level of warehouse characteristics. From the foregoing, the development of methods for the effective use of local raw materials to obtain new structures of two-layer knitted fabrics, the production of knitted products that replace imports from them, meeting competitive, high-quality, internal and external market requirements, is one of the most pressing problems of our time.